Locoregional recurrence of triple-negative breast cancer: effect of type of surgery and adjuvant postoperative radiotherapy - Bayoumi Y (Dove Medical Press, 2014)
Yasser Bayoumi,1 Ayman AbdelSamie,2 Ahmed Abdelsaid,3 Aida Radwan4 1Radiation Oncology, 2Medical Oncology, 3Surgical Oncology, 4Medical Physics, National Cancer Institute, Cairo University, Cairo, Egypt Background/purpose: The aim was to evaluate the prognostic significance of postoperative radiotherapy (PORT) and surgical type on local recurrence-free survival (LRFS) and overall survival (OS) in triple-negative breast cancer (TNBC) in the Egyptian population. Patients and methods: We evaluated 111 patients with stage I–III TNBC diagnosed at our institute during the period from 2004 to 2009. Patients were stratified according to PORT into two groups: a PORT group and a non-PORT group. The influence of PORT and surgical type on LRFS and OS were evaluated. A cross-matching was done to the non-TNBC group of patients to compare the recurrence and survival rates between them and the studied group of TNBC patients. Results: The mean age of TNBC patients at diagnosis was 63±7 years. The majority of the patients had stage III disease (68.5%) and 73% had clinical or pathological positive lymph nodes. Sixty percent (67/111) of patients had modified radical mastectomy and 44/111 (40%) patients had breast-conserving treatment. PORT was given for 63% of patients, while systemic treatment was given in 89% of patients. At the time of analysis, 13 patients (11%) developed local recurrence: five of 70 (7%) in the PORT group and eight of 41 (19.5%) in the non-PORT group. Five-year LRFS for the whole group of patients was 88%±6%, which was significantly affected by PORT. The surgical type did not affect local recurrence significantly. Five-year OS for the whole group was 54%±8%. PORT and surgical type did not affect OS significantly (P-value 0.09 and 0.11, respectively). Five-year LRFS was 88%±6% and 90%±11% for TNBC and non-TNBC patients, respectively (P-value 0.8); however, OS for TNBC was significantly lower than for non-TNBC (P-value 0.04). Conclusion: TNBC is an aggressive entity compared with other non-TNBC, and these patients benefit from PORT significantly to decrease the risk of local recurrence in all stages. However, further large, prospective, randomized trials are warranted. Keywords: triple-negative breast cancer, postoperative radiotherapy, local recurrence-free survival, overall survival